The star-center of the quaternionic numerical range - Carvalho, L.; Diogo, C.; Mendes, S. (Linear Algebra and its Applications, 2020)
In this paper we prove that the quaternionic numerical range is always star-shaped and its star-center is given by the equivalence classes of the star-center of the bild. We determine the star-center of the bild, and consequently of the numerical range, by showing that the geometrical shape of the upper part of the center is defined by two lines, tangents to the lower bild.